2014
DOI: 10.1002/ajh.23881
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction due to essential thrombocythemia and policythemia vera: The missing piece in the puzzle of their increased cardiovascular risk?

Abstract: Myeloproliferative neoplasms are most commonly associated with venous thrombosis. Up to 60% of patients experience a thrombotic event in their lifetimes, including stroke or myocardial infarction. It is unclear whether pathogenetic factors linking essential thrombocythemia (ET) and polycythemia vera (PV) to thrombotic complications do play a role in the risk of coronary artery disease (CAD). We aimed to assess coronary flow reserve (CFR) as a marker of coronary microvascular function in asymptomatic patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
(37 reference statements)
0
9
0
4
Order By: Relevance
“…79 One study observed a significantly higher prevalence of CMD in patients with polycythemia vera and essential thrombocythemia, and an association of abnormal CFR with Janus kinase 2 mutation. 80 …”
Section: Invasive Testingmentioning
confidence: 99%
“…79 One study observed a significantly higher prevalence of CMD in patients with polycythemia vera and essential thrombocythemia, and an association of abnormal CFR with Janus kinase 2 mutation. 80 …”
Section: Invasive Testingmentioning
confidence: 99%
“…Even though myeloproliferative neoplasms are most commonly associated with venous thrombosis, up to 60% of patients experience a thrombotic event in their lifetimes, including stroke or myocardial infarction. We documented CFR reduction in asymptomatic patients with essential thrombocythemia and polycythemia vera [109]. These patients have coronary microvascular dysfunction in absence of clinical conditions suggesting CAD.…”
Section: Beyond Cfrmentioning
confidence: 99%
“…Vasoocclusion represents a phenomenon involving endothelial cell dysfunction, leukocyte activation, platelet activation, and chronic inflammation resulting in multiple adhesive interactions between these cellular elements [111]. Since platelets mediate inflammation as well as thrombosis via release of pro- and anti-inflammatory molecules, they are crucial players to maintain cardiovascular health and to balance different neuroendocrine-immune signals [109]. …”
Section: Beyond Cfrmentioning
confidence: 99%
“…No entanto, os pacientes assintomáticos apresentam disfunção microvascular coronária na ausência de condições clínicas, sugerindo a presença de doença arterial coronariana. Além disso, oclusão coronária, infarto do miocárdio e microtrombos múltiplos do miocárdio sem alterações nas principais artérias coronárias foram descritos (Michiels et al, 1985;Vianello et al, 2015).…”
Section: Aspectos Clínicosunclassified
“…O curso clínico da doença é complicado por episódios trombóticos e hemorrágicos, que ocorrem mais frequentemente em pacientes idosos e naqueles com histórico de eventos vasculares prévios (Finazzi e Harrison, 2005;Vianello et al, 2015).…”
Section: Aspectos Clínicosunclassified